Subtitusi Tepung Tempe dan Penambahan Ekstrak Bunga Telang terhadap Daya Terima Kue Cubit sebagai Jajanan yang Mengandung Antioksidan - Beatrich Laila Siregar; Rita Ismawati (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Tempeh flour and telang flowers are food ingredients that contain antioxidants and can protect body cells from damage. Kue cubit is a snack that is assimilated by the Dutch, the development of which is found to be less visible in terms of its benefits for health, so it is necessary to develop a kue cubit with tempeh flour substitution and the addition of telang flower extract where both ingredients contain antioxidants. This research are to: (1) to determine the effect of tempeh flour substitution and the addition of telang flower extract on acceptability including the parameters of color, aroma, texture, and taste of kue cubit (2) to determine the antioxidant activity in kue cubit substituted with tempeh flour and the addition of telang flower extract from the best formula. This study includes a true experiment using a two-factor factorial Complete Random Design (RAL) research design, they are the variation in the amount of tempeh flour and the variation in the number of telang flowers that will be extracted as much as 40 ml, consisting of 6 formulas. The data were tested using Kruskal wallis if there was an influence followed by using the man whitney test. The results of the analysis showed there were significant differences in each kue cubit formula with color parameters and there were no effect on aroma, texture, and taste parameters. The best formula is X3Y3 (10%: 20gram), with an IC50 antioxidant activity value of 378.355 μg/mL included in the weak category.